Ten Years of Experience Support Pharmacogenetic Testing to Guide Individualized Drug Therapy - María Celsa Peña-Martín; Belén García-Berrocal; Almudena Sánchez-Martín; Elena Marcos-Vadillo; María Jesús García-Salgado; Santiago Sánchez; Carolina Lorenzo; David González-Parra; Francisco Sans; Manuel Franco; Andrea Gaedigk; María José Mateos-Sexmero; et al. (MDPI AG, 2022)
Precision medicine utilizing the genetic information of genes involved in the metabolism and disposition of drugs can not only improve drug efficacy but also prevent or minimize adverse events. Polypharmacy is common among multimorbid patients and is associated with increased adverse events. One of the main objectives in health care is safe and efficacious drug therapy, which is directly correlated to the individual response to treatment. Precision medicine can increase drug safety in many scenarios, including polypharmacy. In this report, we share our experience utilizing precision medicine over the past ten years. Based on our experience using pharmacogenetic (PGx)-informed prescribing, we implemented a five-step precision medicine protocol (5SPM) that includes the assessment of the biological-clinical characteristics of the patient, current and past prescription history, and the patient's PGx test results. To illustrate our approach, we present cases highlighting the clinical relevance of precision medicine with a focus on patients with a complex history and polypharmacy.